TRAINING BY USING ZOOM MEETING TO IMPROVE TEACHING SKILLS AT SDN 017 SUNGAI GANTANG - Jawardi Jawardi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
Basic teaching skills are related to some basic and inherent abilities or skills that every teacher must possess and actualize (Mulyasa, 2013; Achdiani and Rusliyani, 2017). For this reason, training was carried out by using Zoom meetings through the Class Action research method in two cycles. The research was conducted at SDN 017 Sungai Gantang, Kecamatan Kempas, Kabupaten Indragiri Hilir which involved 9 (nine) teachers. The research was conducted for 3 months from March to May 2020. The results of the research in cycle I found that the teacher's ability in teaching skills at SDN 017 Sungai Gantang, Kecamatan Kempas, Kabupaten Indragiri Hilir was categorized as good, but there was one teacher who was still in the sufficient category in the skill of asking questions with a score of 65. It was seen that the asking question skills were not seen, in which the teacher asked for explanations and provided the stimulus to students. Similarly, in the next component, namely the skills of opening and closing lessons, there were some teachers who were still missing due to network constraints so they forgot to give openings in lessons. Data in cycle II illustrated that there were 3 teachers got a good category in teaching and 3 teachers got a very good category in doing online learning. This was the impact of training on teaching skills carried out by school principals as a routine activity in improving teachers’ professionalism.